Halal Certification as a Tool for Women's Economic Empowerment in MSMEs - Harahap, Ade Khadijatul Z; Rahmat, Rahmat (Economic: Journal Economic and Business, 2025)
Halal certification offers various benefits, but the process of obtaining it often faces challenges, especially for MSMEs managed by women. One of the main obstacles is the relatively high cost of certification. This study uses a qualitative approach with a case study technique to deeply understand the role of halal certification in empowering women's economy in the MSME sector. Data were obtained through in-depth interviews with female MSME actors who have been halal certified and direct observation in the field. The results of the study show that women's communities or networks play an important role in supporting the halal certification process through education, collaboration, and moral support. In addition, halal certification has proven to be not only a label, but also an effective marketing strategy, increasing product competitiveness and opening wider market access. This study noted an increase in sales of up to 30% after obtaining halal certification, reflecting the potential of this certification in supporting the growth and sustainability of women's businesses.